2022
DOI: 10.3390/biomimetics7040222
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Nanomembranes as Building Blocks for Nanophotonics, Plasmonics and Metamaterials

Abstract: Nanomembranes are the most widespread building block of life, as they encompass cell and organelle walls. Their synthetic counterparts can be described as freestanding or free-floating structures thinner than 100 nm, down to monatomic/monomolecular thickness and with giant lateral aspect ratios. The structural confinement to quasi-2D sheets causes a multitude of unexpected and often counterintuitive properties. This has resulted in synthetic nanomembranes transiting from a mere scientific curiosity to a positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 212 publications
0
5
0
Order By: Relevance
“…However, additional consideration focusing on alternative design and deployment approaches in array configurations requires further research attention. Jaksic et al, [29] explore the use of bio-inspired intelligent algorithms in designing nanostructured solar cells. In this case, the use of bio-inspired intelligent approaches such as artificial neural networks enable the determination of optical properties of nanophotonic devices i.e., small scale solar cells.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, additional consideration focusing on alternative design and deployment approaches in array configurations requires further research attention. Jaksic et al, [29] explore the use of bio-inspired intelligent algorithms in designing nanostructured solar cells. In this case, the use of bio-inspired intelligent approaches such as artificial neural networks enable the determination of optical properties of nanophotonic devices i.e., small scale solar cells.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of a bioinspired models from a geometrical viewpoint is yet to receive sufficient research consideration. In addition, the use of bio-inspired approaches is recognized to be useful in different aspects associated with solar cells, and solar panels as seen in [26][27][28][29]. Furthermore, the focus of the considered research is shown in Table 1.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In optimization problems, fireflies represent potential solutions, and their brightness corresponds to the quality of the solution. Fireflies move towards brighter neighbors, and the algorithm converges to an optimal solution [92]. The Bat Algorithm (BA) is inspired by the echolocation behavior of bats used for continuous optimization and employs a population of virtual bats that search for solutions in the search space.…”
mentioning
confidence: 99%
“…They used a radial basis function neural network RBF-NN as a surrogate between geometric parammanipulation properties of metamaterials, for example by creating metamaterials with unique refractive indices, or, light-focusing capabilities. Fireflies adjust the parameters of metamaterial elements to achieve desired optical effects[92]. While they are not as popular as ACO and BCO, thereare several 1836 trained to model the relationships between specified de-1837 sign parameters and a range of different material prop-1838 erties [218], [219].…”
mentioning
confidence: 99%